Answer: X=2 and 3 = -1
Step-by-step explanation:Here we will use elimination method to solve the given system of an equation.
We have,
3x+y=5................equation 1
x−2y=4..................equation 2
Note: here we have unequal coefficient for both x and y. So we will first make coefficient of either x or y equal.
Here we well make coefficient of y equal by multiplying equation 1 by 2, we get
6x+2y=10..........equation 3
Now, we have coefficient of y equal with opposite sign, hence it can be eliminated on addition.
Adding equation 2 and 3, we get
x−2y=4
6x+2y=10
−−−−−
7x=14
Now divide both side by 7, we get
or, x=147=2
Plug the value of x= 2 in equation 1, we get
3X2+y=5
or, 6+y=5
Subtract 6 on both side, we get
or, y=5−6